Dynamics of Trust in Guanxi Networks - CHUA, Roy Y. J. (Institutional Knowledge at Singapore Management University, 2006)
Interpersonal trust is an important element of Chinese guanxi network. In this chapter, we examine Chinese guanxi network from a trust perspective. We adopt the distinction that trust could be built on either a socio-emotional basis (affect-based trust) or an instrumental basis (cognition-based trust) and use this lens to examine cultural differences in Chinese and Western social networks. Specifically, we will discuss (a) how the two dimensions of trust are related in the Chinese versus American context, and (b) how affect-based trust is associated with different forms of social exchange in Chinese versus American social networks. Because dyadic relationships are embedded within larger social networks, trust between two network actors is also likely to be influenced by the social context that surrounds them. Hence, we also examine how dyadic trust is shaped by higher-level network properties such as density.